2012
DOI: 10.1177/0022034512440579
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Nanocomposite with Calcium Phosphate and Quaternary Ammonium

Abstract: Secondary caries is a frequent reason for restoration failure, resulting from acidogenic bacteria and their biofilms. The objectives of this study were to: (1) develop a novel nanocomposite containing nanoparticles of amorphous calcium phosphate (NACP) and quaternary ammonium dimethacrylate (QADM); and (2) investigate its mechanical and antibacterial durability. A spray-drying technique yielded NACP with particle size of 116 nm. The nanocomposite contained NACP and reinforcement glass fillers, with QADM in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 32 publications
0
110
0
Order By: Relevance
“…In Dentistry, AgNPs have been studied to control oral biofilm formation in dental restorative materials [9][10][11] , and in dental implants 12 . However, for caries prevention, there is still a lack of evidence--based knowledge to indicate its use as a nonsurgical management of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…In Dentistry, AgNPs have been studied to control oral biofilm formation in dental restorative materials [9][10][11] , and in dental implants 12 . However, for caries prevention, there is still a lack of evidence--based knowledge to indicate its use as a nonsurgical management of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial effect against two E. faecalis strains (ATCC and an endodontic isolate) were assessed, and results had shown that addition of QPEI nanoparticles improved the killing ability of PCS against biofilms of both E. faecalis strains and the effects of AH Plus on the biomass of biofilms from the ATCC strain. Moreover, there were no relevant changes in physicochemical and 95) quaternary ammonium polyethyleneimine QPEI unpolymerizable composite resin 24) , endodontic materials [89][90][91] quaternary ammonium dimethacrylate QADM/IMQ polymerizable composite resin [25][26][27]32) , adhesive system 42) 2-methacryloxylethyl dodecyl methyl ammonium bromide MAE-DB polymerizable composite resin 28,29) 2-methacryloxylethyl hexadecyl methyl ammonium bromide MAE-HB polymerizable composite resin 28,29) 2-Dimethyl-2-dodecyl-1-methacryloxyethyl ammonium iodine DDMAI polymerizable composite resin 30) quaternary ammonium methacrylate QAM polymerizable composite resin 31) , adhesive system 5,53,54) 2-methacryloyloxyethyl phosphorylcholine MPC polymerizable composite resin 33) dimethylaminododecyl methacrylate DMADDM polymerizable adhesive system [43][44][45] quaternary ammonium methacrylate polymer QAMP unpolymerizable adhesive system [46][47][48] methacryloxylethyl cetyl ammonium chloride DMAE-CB polymerizable adhesive system [49][50][51][52] benzalkonium chloride BAC unpolymerizable adhesive system [55][56][57] , glass ionomer cement 73,74) , endodontic materials 87) poly-2-methacry...…”
Section: Endodontic Materialsmentioning
confidence: 99%
“…It has been shown that there is microleakage on restoration margins, and these gaps can be colonized by oral bacteria, thus resulting in secondary caries, which makes the restoration replacement necessary 22,23) . In order to prevent or diminish biofilm accumulation over composite and in the restorations margins, and also to improve the durability of prostheses, antimicrobial restorative materials have been developed, especially through the incorporation of quaternary ammonium to composite resins [24][25][26][27][28][29][30][31][32] . In 2006, a research developed by Beyth et al 24) reported that 1 wt% quaternary ammonium polyethyleneimine (QPEI) nanoparticles immobilized into composite or fluid resin had strong antimicrobial activity upon contact without leach-out of the nanoparticles and compromising in mechanical properties.…”
Section: Composite Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are found to be capable of reducing the number of bacteria that are resistant to other types of cationic antibacterials [15]. The examples of the QAS-containing materials as antibacterials for dental restoratives include incorporation of a methacryloyloxydodecyl pyridinium bromide as an antibacterial monomer into resin composites [12], use of methacryloxylethyl cetyl ammonium chloride as a com-ponent for antibacterial bonding agents [16,17], addition of quaternary ammonium polyethylenimine nanoparticles into composite resins [18][19][20][21][22][23], and incorporation of polyQAS (PQAS) into glass-ionomer cements (GICs) [24]. All these studies found that the QAS-containing materials did exhibit significant antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%